3x-4分之3x-1=6分之x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 09:05:05
3x-4分之3x-1=6分之x3x-4分之3x-1=6分之x3x-4分之3x-1=6分之x3x-4分之3x-1=6分之x=>6*(3x-1)=x*(3x-4)=>18x-6=3x^2-4x=>3x^2
3x-4分之3x-1=6分之x
3x-4分之3x-1=6分之x
3x-4分之3x-1=6分之x
3x-4分之3x-1=6分之x
=>6*(3x-1)=x*(3x-4)
=>18x-6=3x^2-4x
=>3x^2-22x+6=0
=>x=[(11+(-)√103)]/3
(x²-4分之2x)-(x+2分之1)(x²-4分之2)+(x-2分之x)=1x分之3+x-1分之6=x(x-1)分之x-3
X+4分之1-X+7分之1=X+3分之1-X+6分之1 求X
x+1分之2x=1 x-2分之x-x^2-4分之1=1 x+3分之5=x分之2 x-2分之6=x+3分之x -1
解方程:x+1分之x+2-x+3分之x+4=x+5分之x+6-x+7分之x+8
x+1分之x+2减去x+3分之x+4=x+5分之x+6减去X+7分之x+8 (解方程)
方程:x+1分之x+2-x+3分之x+4=x+5分之x+6-x+7分之x+8
一道分式方程.X-2分之X-1减X-3分之X-2=X-5分之X-4减X-6分之X-5.要具体.
解方程;3分之x+x-1分之6=x(x-1)分之x+5
x²+x分之2+x²-x分之3=x平方-1分之4
6分之x-2=x分之x+3-1
4分之x+3=x-5分之x-1
4分之x+3=x-5分之x-1
2分之1x-6=4分之3x
4分之3x-6分之1x=84
4分之3x+6分之1x=15
x+2分之x=x-1分之x x平方+x分之4=x+1分之6-x分之1 x-3分之2x-1=1-3-x分之5x+2分之x=x-1分之x x平方+x分之4=x+1分之6-x分之1 x-3分之2x-1=1-3-x分之5 (x+2分之3x-x+2分之x)/x平方-4分之x(x-1)=4
5分之3x一7>=2分之x-2,4分之x一12分之2x一1>6分之1一3分之x
(1) x-2分之4x-1=2-x分之3 (2) x-3分之x-2x-6分之1=2分之1 (3) x+3分之x=1+x-1分之2 解分式方程